2020
DOI: 10.1093/infdis/jiaa549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Water, Sanitation, Handwashing, and Nutrition Interventions on Enteropathogens in Children 14 Months Old: A Cluster-Randomized Controlled Trial in Rural Bangladesh

Abstract: Background We evaluated the impact of low-cost water, sanitation, handwashing (WSH) and child nutrition interventions on enteropathogen carriage in the WASH Benefits cluster-randomized controlled trial in rural Bangladesh. Methods We analyzed 1411 routine fecal samples from children 14±2 months old in the WSH (n = 369), nutrition counseling plus lipid-based nutrient supplement (n = 353), nutrition plus WSH (n = 360), and cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(56 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…Most studies of onsite sanitation interventions have occurred in rural areas. Despite good evidence that onsite sanitation is associated with reductions in diarrheal disease ( Freeman et al, 2017a ; Wolf et al, 2018 ), several recent rural trials of basic sanitation and combined WASH interventions with good uptake and use reported mixed effects on child health outcomes including diarrhea, linear growth, and more recently, enteric infection ( Ercumen et al, 2019 ; Grembi et al, 2020 ; Sanitation Hygiene Infant Nutrition Efficacy (SHINE) Trial Team et al, 2019 ; Lin et al, 2018 ; Luby et al, 2018 ; Null et al, 2018 ; Pickering et al, 2019 ; Rogawski McQuade et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of onsite sanitation interventions have occurred in rural areas. Despite good evidence that onsite sanitation is associated with reductions in diarrheal disease ( Freeman et al, 2017a ; Wolf et al, 2018 ), several recent rural trials of basic sanitation and combined WASH interventions with good uptake and use reported mixed effects on child health outcomes including diarrhea, linear growth, and more recently, enteric infection ( Ercumen et al, 2019 ; Grembi et al, 2020 ; Sanitation Hygiene Infant Nutrition Efficacy (SHINE) Trial Team et al, 2019 ; Lin et al, 2018 ; Luby et al, 2018 ; Null et al, 2018 ; Pickering et al, 2019 ; Rogawski McQuade et al, 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…The sanitation-only arm had no impact on any parasite measured, although T. trichiura was too infrequently detected to estimate effects ( Pickering et al, 2019 ). An evaluation of a comprehensive suite of 34 enteric pathogens reported reduced prevalence and quantity of enteric viruses, but not bacteria or parasites, among children aged 14 months old in the combined WASH arms in the Bangladesh trial ( Grembi et al, 2020 ). Together with our findings, these results suggest that sanitation and combined WASH interventions can reduce the prevalence of enteric infection in some settings but that effects may vary by pathogen, child age, intervention, and setting.…”
Section: Discussionmentioning
confidence: 99%
“…Evidences noticed that handwashing with soap eliminates transient potentially pathogenic organisms from the hands through the in uences of microbial effectiveness [35], despite a complete change of handwashing behavior remains challenged [37]. Particularly handwashing before preparing food is a mostly imperative opportunity to avert CHD that appears to be a primary means of prevention where intervened households had a lower prevalence of CHD [38,39]. Moreover, compared with controls, children in households with plain soap had a 53% lower incidence of CHD in Karachi, Pakistan [40].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of onsite sanitation interventions have occurred in rural areas. Despite good evidence that onsite sanitation is associated with reductions in diarrheal disease (M. C. Freeman et al, 2017; Wolf et al, 2018), several recent rural trials of basic sanitation and combined WASH interventions with good uptake and use reported mixed effects on child health outcomes including diarrhea, linear growth, and more recently, enteric infection (Ercumen et al, 2019; Grembi et al, 2020; Humphrey et al, 2019; Lin et al, 2018; Luby et al, 2018; Null et al, 2018; Pickering et al, 2019; Rogawski McQuade, Platts-Mills, et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The sanitation-only arm had no impact on any parasite measured, though T. trichiura was too infrequently detected to estimate effects (Pickering et al, 2019). An evaluation of a comprehensive suite of 34 enteric pathogens reported reduced prevalence and quantity of enteric viruses, but not bacteria or parasites, among children aged 14 months old in the combined WASH arms in the Bangladesh trial (Grembi et al, 2020). Together with our findings, these results suggest that sanitation and combined WASH interventions can reduce the prevalence of enteric infection in some settings but that effects may vary by pathogen, child age, intervention, and setting.…”
Section: Discussionmentioning
confidence: 99%